2022
DOI: 10.3390/insects13090847
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Compaction, Temperature, and Duration Factors for Packaging and Transporting of Sterile Male Aedes aegypti (Diptera: Culicidae) under Laboratory Conditions

Abstract: Optimized conditions for the packaging and transportation of sterile males are crucial factors in successful SIT programs against mosquito vector-borne diseases. The factors influencing the quality of sterile males in packages during transportation need to be assessed to develop standard protocols. This study was aimed to investigate the impact of compaction, temperature, and duration factors during packaging and transportation on the quality of gamma-sterilized male Ae. aegypti. Aedes aegypti males were steri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Beyond addressing our project’s specific needs, the backpack described herein may also have other uses. For example, the implementation of the sterile insect technique (SIT) for mosquito control always involve the transportation of live specimens from the production facility to the release points and sometimes beyond the reach of motorized transport (Ernawan et al, 2022; Gómez et al, 2022). Specifically, for SIT procedures, other factors apart from transportation such as packaging and storage conditions may affect the survival and longevity of mosquitoes(Chung et al, 2018; Sasmita et al, 2022), and any potential role for carrier backpacks based on this prototype would probably be limited to parts of remote rural areas or dense urban settlements that may be more readily accessed on foot.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond addressing our project’s specific needs, the backpack described herein may also have other uses. For example, the implementation of the sterile insect technique (SIT) for mosquito control always involve the transportation of live specimens from the production facility to the release points and sometimes beyond the reach of motorized transport (Ernawan et al, 2022; Gómez et al, 2022). Specifically, for SIT procedures, other factors apart from transportation such as packaging and storage conditions may affect the survival and longevity of mosquitoes(Chung et al, 2018; Sasmita et al, 2022), and any potential role for carrier backpacks based on this prototype would probably be limited to parts of remote rural areas or dense urban settlements that may be more readily accessed on foot.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, and based on our findings, we suggest that sterile males are immobilized at temperatures higher than 4 °C, and to investigate which time–temperature combination will be the least harmful to them. Temperatures between 5 and 10 °C for less than 3 h were recommend 33 , and it was suggested immobilising the males at 7-10 °C for a short period 26 , moreover, Ernawan et al 34 advise to use a temperature of 7 °C for a period that does not exceed 24 h. Within the context of our study, it would be recommended to evaluate the exposure of the mosquitoes to temperatures in the range 4-10 °C for 10–25 min, and to determine the effect on survival, escape ability, and sexual competitiveness under semi-field conditions using standardised protocols, which would allow comparison with other studies. Also, it would be recommended to make improvements in the design of the emergence chamber, so that the first chilling process can be eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…Transboundary shipments of mosquitoes by air may take more than 24 h [ 8 , 9 ] and recent studies have shown contrasting results for mosquitoes transported as pupae or as chilled or nonchilled sterile males. Furthermore, in these studies, the results were relevant for transportation lasting no more than 24 h [ 9 , 10 , 11 , 12 , 13 , 14 ]. In contrast, operational fruit fly SIT programs entail the long-distance transportation of pupae under different atmospheric conditions (for 67 h to 89 h) without impacting the quality of the flies [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%